2022
DOI: 10.1177/17455057221092268
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use and distribute HIV self-test kits to clients and partners: A qualitative analysis of female sex workers’ collective opinion and attitude in Côte d’Ivoire, Mali, and Senegal

Abstract: Background: In West Africa, female sex workers are at increased risk of HIV acquisition and transmission. HIV self-testing could be an effective tool to improve access to and frequency of HIV testing to female sex workers, their clients and partners. This article explores their perceptions regarding HIV self-testing use and the redistribution of HIV self-testing kits to their partners and clients. Methods: Embedded within ATLAS, a qualitative study was conducted in Côte-d’Ivoire, Mali, and Senegal in 2020. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Other experiences of secondary distribution have been reported in Southern and Eastern Africa: it was acceptable and allowed to reach clients of FSW [ 41 , 46 ], partners of MSM [ 47 ], or partners of pregnant women [ 42 , 48 , 49 ]. Within ATLAS, a qualitative survey conducted showed that FSW were willing to redistribute the HIVST to their regular partners and clients [ 50 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Other experiences of secondary distribution have been reported in Southern and Eastern Africa: it was acceptable and allowed to reach clients of FSW [ 41 , 46 ], partners of MSM [ 47 ], or partners of pregnant women [ 42 , 48 , 49 ]. Within ATLAS, a qualitative survey conducted showed that FSW were willing to redistribute the HIVST to their regular partners and clients [ 50 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Further details on the ATLAS project can be found in the research protocol [25]. Further, project's results have been published on stakeholders' attitudes and perceptions on HIVST in West Africa [21], the relevance of HIVST secondary distribution to resilient testing services [16], challenges faced by HIVST secondary distribution in contexts of low disclosure of HIV test result [26], FSW's willingness to distribute HIVST kits [27], and the impact of HIVST in Côte d'Ivoire [28]. Cost and scale-up costs of integrating HIVST in community-led programs for key population were also published [29].…”
Section: Study Contextmentioning
confidence: 99%
“…ATLAS aimed to address the diagnosis gap and evaluate the potential impact of HIVST in Côte d'Ivoire, Mali and Senegal, 20 with an emphasis on secondary distribution of HIVST whereby KP directly reached by the programme could re-distribute some of their HIVST kits to their sexual partners, clients, and/or peers. [20][21][22] In addition to the distribution of a total of 380 000 self-test kits to people at higher risk of HIV (of which 340 000 were distributed through activities targeting FSW and MSM) over 2019-2021, the programme included different work packages to understand the practicality, costs and populationlevel impact of HIVST, combining population studies, 11,23 qualitative studies, 21,24,25 economic analyses, 26 and mathematical modelling.…”
Section: Introductionmentioning
confidence: 99%